2018
DOI: 10.1016/j.tem.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Extragonadal Effects of Follicle-Stimulating Hormone on Osteoporosis and Cardiovascular Disease in Women during Menopausal Transition

Abstract: The risk of osteoporosis and cardiovascular disease increases significantly in postmenopausal women. Until recently, the underlying mechanisms have been primarily attributed to estrogen decline following menopause. However, follicle-stimulating hormone (FSH) levels rise sharply during menopausal transition and are maintained at elevated levels for many years. FSH receptor has been detected in various extragonadal sites, including osteoclasts and endothelial cells. Recent advances suggest FSH may contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 82 publications
2
48
0
Order By: Relevance
“…Although the FSH ( β = −10.81, p = 0.037) and estradiol ( β = 46.23, p = 0.043) levels were statistically different, all values remained normal ranges for peri- or post-menopausal women (lower part of Table 2 ). We note that, the FSH level rises above 40 mIU/mL during menopause [ 30 ], while estradiol level decreases from 30 to 400 pg/mL to 0–30 pg/mL [ 31 ]. We also note that the changes were opposite in the placebo and KM groups, indicating a potential protective capacity KM to suppress the hormonal changes in menopause.…”
Section: Resultsmentioning
confidence: 99%
“…Although the FSH ( β = −10.81, p = 0.037) and estradiol ( β = 46.23, p = 0.043) levels were statistically different, all values remained normal ranges for peri- or post-menopausal women (lower part of Table 2 ). We note that, the FSH level rises above 40 mIU/mL during menopause [ 30 ], while estradiol level decreases from 30 to 400 pg/mL to 0–30 pg/mL [ 31 ]. We also note that the changes were opposite in the placebo and KM groups, indicating a potential protective capacity KM to suppress the hormonal changes in menopause.…”
Section: Resultsmentioning
confidence: 99%
“…Natural menopause causes altered expression of progesterone, testosterone and estrogen, while these hormones, such as estrogen can regulate the expression of certain lncRNAs [16,17]. In addition, the development of osteoporosis after menopause is also affected by dysregulated expression of hormones [18]. Therefore, the down-regulated SNHG1 after menopause and during the development of osteoporosis may be also caused by the changed levels of hormones.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the accelerated rise in FSH across the menopause transition may have independent adverse effects on the vasculature (Zhu et al. ). A recent study demonstrated that administration of FSH increased atherosclerotic lesions and serum concentrations of vascular cell adhesion molecule‐1 (VCAM‐1) in ovariectomized ApoE knockout mice, which was independent of estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%